2024
DOI: 10.1051/0004-6361/202347411
|View full text |Cite
|
Sign up to set email alerts
|

Extreme N-emitters at high redshift: Possible signatures of supermassive stars and globular cluster or black hole formation in action

R. Marques-Chaves,
D. Schaerer,
A. Kuruvanthodi
et al.

Abstract: Context. Recent James Webb Space Telescope (JWST) spectroscopic observations of the z = 10.6 galaxy GN-z11 have revealed a very peculiar UV spectrum exhibiting intense emission lines of nitrogen, which are not typically detected in galaxy spectra. This observation indicates a super-solar N/O abundance ratio at low metallicity, which only resembles the abundances seen in globular cluster (GC) stars. This discovery suggests that we might be seeing proto-GCs in formation or possibly even signatures of supermassiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…While their nature likely varies, some other high-redshift detections of prominent N III] and N IV] emission lines beyond GN-z11 and the Sunburst Arc (Section 4.3) may hint at similar conditions. If globular clusters are a major source of UV light at z > 6 (e.g., Boylan-Kolchin 2018), it is likely that other precursor systems will be caught at similar phases to GN-z11 especially among UV-selected samples (and initial searches for such objects have already revealed other reionization era candidates; Isobe et al 2023b;Marques-Chaves et al 2024), enabling more detailed investigation of the timescales and processes involved in building up their stellar mass and peculiar abundances. The possible presence of an accreting black hole in GN-z11 (Maiolino et al 2024, see Section 3.3) also hints at the potential importance of such dense highly clustered star-forming environments for seeding and growing massive black holes (e.g., Portegies Zwart & McMillan 2002), and the significance of constraining these processes directly at z > 6.…”
Section: Discussion and Summary: Gn-z11 As A Potential Globular Clust...mentioning
confidence: 99%
“…While their nature likely varies, some other high-redshift detections of prominent N III] and N IV] emission lines beyond GN-z11 and the Sunburst Arc (Section 4.3) may hint at similar conditions. If globular clusters are a major source of UV light at z > 6 (e.g., Boylan-Kolchin 2018), it is likely that other precursor systems will be caught at similar phases to GN-z11 especially among UV-selected samples (and initial searches for such objects have already revealed other reionization era candidates; Isobe et al 2023b;Marques-Chaves et al 2024), enabling more detailed investigation of the timescales and processes involved in building up their stellar mass and peculiar abundances. The possible presence of an accreting black hole in GN-z11 (Maiolino et al 2024, see Section 3.3) also hints at the potential importance of such dense highly clustered star-forming environments for seeding and growing massive black holes (e.g., Portegies Zwart & McMillan 2002), and the significance of constraining these processes directly at z > 6.…”
Section: Discussion and Summary: Gn-z11 As A Potential Globular Clust...mentioning
confidence: 99%
“…They suggest an intimate connection between black hole feedback and rapid (massive) star formation, indicative of what is often referred to as positive feedback, because the chemical timescales must be relatively short. This connection, resulting in the speed-up of chemical evolution, would be further enhanced by including the effects of stellar tidal disruptions as suggested to account for the relative-to-solar nitrogen-to-carbon abundance ratio enhancement and abundance pattern consistent with a single stellar tidal disruption event in a nearby AGN (Miller et al 2023), or by the possible role of very massive or even supermassive stars (Marques-Chaves et al 2024;Vink 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to oxygen, strong emission lines associated with other elements are now being clearly detected at z > 4 (e.g., Arellano-Córdova et al 2022a;Isobe et al 2023b;Jones et al 2023;Nakajima et al 2023;Marques-Chaves et al 2024). An example includes Ne, S, and Ar, which are the most typical α-elements observed in nebular studies in the local Universe (Izotov et al 2006;Croxall et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical abundances of SFGs have been studied in surveys like CEERS, GLASS, and JADES (Treu et al 2022;Finkelstein et al 2023;Eisenstein et al 2024). For example, the abundance ratio of C/O has been reported in a few galaxies at z > 6 (e.g., Jones et al 2012;Arellano-Córdova et al 2022a;Cameron et al 2023b;Marques-Chaves et al 2024), while the chemical abundances of Ne, S, and Ar have been determined for multiple SFGs at z = 4-8 (e.g., Isobe et al 2023a). Arellano-Córdova et al (2022a) reported Ne/O abundance ratios for three galaxies at z > 7 using spectra from the JWST Early Release Observations (ERO; Pontoppidan et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation